Congenital cholesteatoma: a review - Swain, Santosh Kumar (International Journal of Advances in Medicine, 2022)
Congenital cholesteatoma (CC) is a whitish mass lesion found in the middle ear cleft behind the intact tympanic membrane in early life. It is a relatively uncommon disease and shows its growth and extension over a period of time. CC is evidenced with no prior history of tympanic membrane perforation, otorrhea, previous otologic procedures, normal pars tensa, and pars flaccida. The etiopathogenesis of CC is still controversial; however, the epithelial cell rest theory is the most commonly accepted one. The most common sites of CC are the anterior-superior and posterior-superior quadrants of the tympanic cavity. The most common clinical presentation of CC is conductive hearing loss. Early detection and intervention are needed to avoid the complications of CC. The treatment of choice in CC is still surgical. The frequency of recurrence seems to be lower in patients with CC than in acquired cholesteatoma. Rapid progression of the CC may occur in older children and the recurrence has been associated with advanced progression of the cholesteatoma. There are very few reports for CC available in the medical literature This objective of this review article is to discuss the prevalence, etiopathology, clinical manifestations, diagnosis, and treatment.